1993
DOI: 10.1029/92ja01971
|View full text |Cite
|
Sign up to set email alerts
|

EXOS D (Akebono) suprathermal mass spectrometer observations of the polar wind

Abstract: We report observations of the H+, He+, and O+ polar wind ions in the polar cap (>80° invariant latitude, ILAT) above the collision‐dominated altitudes (>2000 km), from the suprathermal mass spectrometer (SMS) on EXOS D (Akebono). SMS regularly observes low‐energy (a few eV) upward ion flows in the high‐altitude polar cap, poleward of the auroral oval. The flows are typically characteristic of the polar wind, in that they are field‐aligned and cold (Ti < 104 °K), and the parallel (field‐aligned) velocities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
145
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(173 citation statements)
references
References 31 publications
27
145
1
Order By: Relevance
“…This has been evidenced by many observational studies and models (Abe et al, 1993;Su et al, 1998a, b;Glocer et al, 2012;Maes et al, 2015). Maes et al (2015), studying outflow above smallscale polar cap arcs using Cluster (Escoubet et al, 2001) measurements, found that the upflow above the polar cap can be roughly divided into two distinct groups based on the solar zenith angle (SZA) of the footpoint of the field line in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been evidenced by many observational studies and models (Abe et al, 1993;Su et al, 1998a, b;Glocer et al, 2012;Maes et al, 2015). Maes et al (2015), studying outflow above smallscale polar cap arcs using Cluster (Escoubet et al, 2001) measurements, found that the upflow above the polar cap can be roughly divided into two distinct groups based on the solar zenith angle (SZA) of the footpoint of the field line in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The low energization also means that it is very difficult for O + ions to escape Earth's gravitational potential via this mechanism, and so very little O + is expected in the polar wind. Nevertheless, O + ions have been observed above the polar caps and in the lobes (Nagai et al, 1984;Waite Jr. et al, 1985;Abe et al, 1993;Su et al, 1998a). Many additional mechanisms have been proposed to explain this (see, e.g., Tam et al, 2007, for an overview).…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations with satellites such as Akebono (EXOS-D) and GEOTAIL have shown that thermal ions, including not only light ions H + and He + but also heavy ions O + and NO +¯o w out of the polar ionosphere and they are found in the lower magnetosphere (Watanabe et al, 1992;Abe et al, 1993a, b;Yau et al, 1991Yau et al, , 1993Yau et al, , 1995 and in the lobe magnetosphere (Mukai et al, 1994;Hirahara et al, 1996;Seki et al, 1996Seki et al, , 1998. A very comprehensive review of the terrestrial plasma source obtained from the DE mission was given by Chappell (1988).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that oxygen ions of low charge state are originated from the terrestrial ionosphere (cf. Abe et al, 1993;André and Yau, 1997;Nilsson et al, 2006) and that they follow various fates; for instance, some of them escape into the distant tail, and…”
Section: Introductionmentioning
confidence: 99%